1989
DOI: 10.1002/jmv.1890280409
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus deoxyribonucleic acid by filter in situ hybridization during pregnancy

Abstract: Samples taken from 101 healthy pregnant women (49 over and 52 under the 20-week gestational period) and 108 healthy nonpregnant women were tested for human papillomavirus (HPV) types. Using 6, 11, 16, and 18 HPV DNA probes, 3-5 x 10(5) exfoliated cells scraped from the cervix were tested by filter in situ hybridization (FISH). Thirty-five of the pregnant women (34.6%) had evidence of the presence of HPV DNA: with 11.8% (12/101) HPV 6; 7.9% (8/101) HPV 11; 8.9% (9/101) HPV 16; and 5.9% (6/101) HPV 18 positivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The HPV detection rate in this study is lower in comparison with that reported (23%) by Chabaud et al [14] in the cytologically normal group. The high percentage observed, as the authors noted, could be due to an increase in the HPV detection rate in pregnant women with respect to the general population [32], possibly because of viral reactivation during pregnancy.…”
Section: Discussionmentioning
confidence: 80%
“…The HPV detection rate in this study is lower in comparison with that reported (23%) by Chabaud et al [14] in the cytologically normal group. The high percentage observed, as the authors noted, could be due to an increase in the HPV detection rate in pregnant women with respect to the general population [32], possibly because of viral reactivation during pregnancy.…”
Section: Discussionmentioning
confidence: 80%
“…It has been suggested that pregnancy could increase the risk of HPV infection due to pregnancy-related hormonal changes and/or immunosuppression [1] , but the majority of the reports do not substantiate this conclusion [5][6][7][8][9][10][11] . Similarly, in some studies, cervical HPV carriage was shown to increase with increasing gestational age [1][2][3]12] , whereas other studies failed to demonstrate this trend [9,13] .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of pregnancy on human papillomavirus (HPV) carriage has been a controversial issue [1][2][3][4] . It has been suggested that pregnancy could increase the risk of HPV infection due to pregnancy-related hormonal changes and/or immunosuppression [1] , but the majority of the reports do not substantiate this conclusion [5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…An increase of HPV infections during pregnancy followed by a decrease post partum is also the subject of controversy [148,149,153,154]. Early age at first delivery seems to be an indepen dent risk factor for the development of cervical cancer (OR: 5.0) when comparing women younger than 16 years with women older than 24 years in a consensus PCRbased case-control study [128].…”
Section: Pregnancy and The Menstrual Cyclementioning
confidence: 99%